2019
DOI: 10.1111/andr.12578
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of perineural invasion in patients with de novo metastatic prostate cancer

Abstract: Background:The clinical value of perineural invasion (PNI) in patients with localized prostate cancer (PCa) is widely explored. However, its role in metastatic PCa (mPCa) remains unknown. Objectives: We aim to investigate the clinical significance of PNI in patients with mPCa. Materials and methods: Data of 515 mPCa patients between 2012 and 2018 were retrospectively studied. PNI and its intensity were identified by prostate biopsy. The prognostic value of PNI was evaluated by Kaplan-Meier curves and Cox propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
7
1
Order By: Relevance
“…Our results showed that 30.5% of patients had PNI, while the incidence in other research ranged from 21.1 to 50.2% [ 13 , 27 30 ]. The variation between these studies may be associated with different patient groups or pathological criteria.…”
Section: Discussioncontrasting
confidence: 41%
“…Our results showed that 30.5% of patients had PNI, while the incidence in other research ranged from 21.1 to 50.2% [ 13 , 27 30 ]. The variation between these studies may be associated with different patient groups or pathological criteria.…”
Section: Discussioncontrasting
confidence: 41%
“…Neoplastic cells infiltrating into the perineurium space were spared by tumor resection, leading to local recurrence (31). PNI has been reported as an important danger factor for independent survival, indicating poor prognosis for many malignancies, including prostate cancer (32)(33)(34), colon cancer (35)(36)(37), head and neck cancer (38), gastric cancer (39), and cervical cancer (40). In cervical cancer, PNI could be considered as an indication guiding the operation and postoperative adjuvant therapy (41).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Ciftci et al (43) reported that biopsy PNI was associated with increased bone metastasis in PCa. In addition, Zhao et al (44) found that multifocal PNI in biopsy specimen was an independent adverse prognosticator for both castration-resistant PCafree survival and OS in patients with favorable/intermediate-risk metastatic PCa patients when compared to PNI-patients. However, due to the present under-reporting of PNI in clinical practice which hampered the precise evaluation of its true clinical significance, it was reported that only 43% of all the urologists would consider biopsy PNI in pathology reports to have an influence on their decisions when selecting treatment options for PCa patients.…”
Section: Discussionmentioning
confidence: 99%